Looking, Feeling, and Doing: Are There Age Differences in Attention, Mood and Behavioral Responses to Skin Cancer Information? - Isaacowitz, Derek M. (2011)
OVERVIEW: Previous studies on aging and attention to emotional information found that older adults may look away from negative stimuli to regulate their moods. However, it is an open question whether older adults’ tendency to look less at negative material comes at the expense of learning when negative information is also health-relevant. This study investigated how age-related changes in attention to negative but relevant information about skin cancer risk reduction influenced both subsequent health behavior and mood regulation. METHODS: Younger (18-25, n = 78) and older (60-92, n = 77) adults’ fixations toward videos containing negatively-valenced content and risk-reduction information about skin cancer were recorded with eye-tracking. Self-reported mood ratings were measured throughout. Behavioral outcome measures (e.g., answering knowledge questions about skin cancer, choosing a sunscreen, completing a skin self-exam) assessed participants’ learning of key health-relevant information, their interest in seeking additional information, and their engagement in protective behaviors. RESULTS: Older adults generally looked less at the negative video content, more rapidly regulated their moods, and learned fewer facts about skin cancer; yet, they engaged in a greater number of protective behaviors than did younger adults. CONCLUSIONS: Older adults may demonstrate an efficient looking strategy that extracts important information without disrupting their moods, and they may compensate for less learning by engaging in a greater number of protective behaviors. Younger adults may be distracted by disruptions to their mood, constraining their engagement in protective behaviors.